2017
DOI: 10.1126/scitranslmed.aaf1283
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial virulence phenotypes of Escherichia coli and host susceptibility determine risk for urinary tract infections

Abstract: Urinary tract infections (UTIs) are caused by uropathogenic Escherichia coli (UPEC) strains. In contrast to many enteric E. coli pathogroups, no genetic signature has been identified for UPEC strains. We conducted a high-resolution comparative genomic study using E. coli isolates collected from the urine of women suffering from frequent recurrent UTIs. These isolates were genetically diverse and varied in urovirulence, or the ability to infect the bladder of a mouse model of cystitis. Importantly, we found no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
142
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(163 citation statements)
references
References 94 publications
16
142
1
4
Order By: Relevance
“…The flhDC promoter region of these strains was sequenced after PCR amplification and shown to lack insertion elements. About 75% of UPEC strains are in group B2 of the Clermont classification scheme (32, 33), but the strains in this study—UTI89, PNK_004, and PNK_006—were in groups B2, D, and A, respectively. Although the NPEC-S strains and PNK_006 are in the same clade, they have different types of surface motility, which indicates that membership in a specific group cannot account for the difference in surface motility.…”
Section: Resultscontrasting
confidence: 61%
“…The flhDC promoter region of these strains was sequenced after PCR amplification and shown to lack insertion elements. About 75% of UPEC strains are in group B2 of the Clermont classification scheme (32, 33), but the strains in this study—UTI89, PNK_004, and PNK_006—were in groups B2, D, and A, respectively. Although the NPEC-S strains and PNK_006 are in the same clade, they have different types of surface motility, which indicates that membership in a specific group cannot account for the difference in surface motility.…”
Section: Resultscontrasting
confidence: 61%
“…This finding should cause us to reconsider “pathogenicity” since, at the genomic level these bacteria are identical (at least by the sequence of the 16S rRNA gene). For E. coli , other investigators have recently shown that there is no genomic difference between strains associated with UTI or no UTI; the investigators report that the differences appear related to transcription rather than core genetics 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that OmpT from the UPEC strain CFT073 is involved in adhesion, invasion, and/or inactivation of AMPs (Brannon et al, 2013;He et al, 2015). While the presence of ompT is associated with virulent strains, its precise contribution remains unclear, as UPEC clinical isolates have highly variable genetic sequences (Schreiber et al, 2017). In addition, we previously observed large differences in OmpT protein activity due to differential ompT expression (Thomassin, Brannon, Gibbs, et al, 2012;Thomassin, Brannon, Kaiser, et al, 2012), suggesting that the presence of the ompT gene may not entirely correlate with its activity levels in different UPEC clinical isolates.…”
Section: Discussionmentioning
confidence: 99%